2013
DOI: 10.1371/journal.pone.0072391
|View full text |Cite|
|
Sign up to set email alerts
|

A High Throughput In Vivo Assay for Taste Quality and Palatability

Abstract: Taste quality and palatability are two of the most important properties measured in the evaluation of taste stimuli. Human panels can report both aspects, but are of limited experimental flexibility and throughput capacity. Relatively efficient animal models for taste evaluation have been developed, but each of them is designed to measure either taste quality or palatability as independent experimental endpoints. We present here a new apparatus and method for high throughput quantification of both taste qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 50 publications
(57 reference statements)
1
12
0
Order By: Relevance
“…The brief access assay also has been used to establish concentration-response functions for appetitive tastants such as sweeteners. Sucrose potencies determined from concentration-response functions for sucrose using Sprague-Dawley rats have been shown to range narrowly between 40 and approximately 150 mM (Grobe and Spector, 2008;Palmer et al, 2013;Hashimoto and Spector, 2014). This range is consistent with the only published concentration-response function for rTAS1R2/3 (Nelson et al, 2001) found for this review.…”
Section: A Animal Modelssupporting
confidence: 85%
See 4 more Smart Citations
“…The brief access assay also has been used to establish concentration-response functions for appetitive tastants such as sweeteners. Sucrose potencies determined from concentration-response functions for sucrose using Sprague-Dawley rats have been shown to range narrowly between 40 and approximately 150 mM (Grobe and Spector, 2008;Palmer et al, 2013;Hashimoto and Spector, 2014). This range is consistent with the only published concentration-response function for rTAS1R2/3 (Nelson et al, 2001) found for this review.…”
Section: A Animal Modelssupporting
confidence: 85%
“…The heterodimeric functional receptor was responsive to a broad variety of compounds, across multiple chemical classes, reflective of the great variety of compounds that are detected as sweet tasting. Those cell lines expressing rat versions of the receptor were not responsive to the human sweeteners aspartame, cyclamate, and the protein thaumatin, consistent with the lack of sensitivity to these compounds by rodents in behavioral assays (Bachmanov et al, 2001;Palmer et al, 2013). This species-dependence of responsiveness to sweeteners has been exploited to identify likely agonist binding sites within the structure of the receptor (Jiang et al, 2004(Jiang et al, , 2005aZhang et al, 2010).…”
Section: E Recombinant Cell-based Assays For Tas1r2/r3 Receptorsmentioning
confidence: 68%
See 3 more Smart Citations